Photo-thermoinduced changes of transmission spectra of As₄₀-xSbxS₆₀ amorphous layers - Rubish, V.M.; Gera, E.B.; Pop, M.M.; Maryan, V.M.; Kostyukevych, S.O.; Moskalenko, N.L.; Semak, D.G.; Kostyukevych, K.V.; Kryuchin, A.A.; Petrov, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
The results of investigation of the As₄₀-xSbxS₆₀ (x = 0-10) thin films
transmission spectra depending on exposure and heat treatment conditions are given. It
was established that illumination and annealing of films leads to the absorption edge shift
into the longwave spectral region. The values of pseudogap width Eg are determined.
Optical characteristic changes of films are caused by photo-thermostructural
transformations taking place in them under irradiation and annealing.